Sanitation and safety while conducting a practical class among Undergraduate Vocational Education (Catering), UTHM - Ismail, Lisa Mariam Syawal; Tukiran, Nor Anis Intan Aqiah; Mohd Nasir, Muhammad Nur Hazim (Penerbit UTHM, 2021)
Food is a necessity for humankind in gaining the energy and substance to live their normal lives. According to Maslow (1955) through his pyramid hieraki he developed that food essentially serves as an essential core to meet hunger and to meet the biological needs of humans for survival. The Malaysian food service industry is becoming more and more rapidly growing which can be seen as a phenomenon for the culinary industry to grow as mushrooms as trends and lifestyle changes prefer to enjoy food from the outside especially among urban residents (Yee & Yuen, 2014).